Modeling Permeation of CO2/CH4, N2/CH4, and CO2/Air Mixtures across a DD3R Zeolite Membrane - van den Bergh, Johan; Mittelmeijer-Hazeleger, Marjo; Kapteijn, Freek (Journal of physical chemistry. C, 2010)
Single component (CO2, CH4, and N2) and equimolar binary mixture (CO2/CH4, N2/CH4, and CO2/Air) permeation data across a disk-shaped all-silica DDR zeolite membrane have been the subject of a thorough modeling study over a challenging broad temperature (220−373 K) and feed pressure (101−1500 kPa) range. The mass transport through the zeolite layer is evaluated for two rival, Maxwell Stefan-based, models: the Relevant Site Model (RSM) and the so-called Reed Ehrlich (RE) approach. Both models have been introduced to account for the strong loading dependency of the diffusivity in small-pore cage-like zeolites like DDR. High pressure adsorption isotherms (up to 7000 kPa) measured on DDR crystals are incorporated to describe adsorption on the zeolite. Both the RSM as the RE approach yield an excellent model fit of the single component permeation data. However, for both models the N2 and CH4 data did not allow an accurate estimation of the model fit parameters. Both models can lead to a good prediction of comparable quality of the mixture permeation data based on the single component model fit parameters. The RE approach is very sensitive toward the model input parameters and the estimated mixture loading, which both can be very hard to determine accurately in practice. The RSM does not suffer from both these issues, which is an evident advantage with respect to application of this model.